Optimal Searching-Based Reference Current Computation Algorithm for IPMSM Drives Considering Iron Loss - Péter Stumpf; Tamás Tóth-Katona (Actuators, 2024)
Interior permanent magnet synchronous machines (IPMSMs) are widely used as traction motors in the electric drive-train because of their high torque-per-ampere characteristics and potential for wide field weakening operation to expand the constant power range. The paper aims to introduce the most important equations to calculate the operating trajectories of an IPMSM for optimal control. The main contribution is that the optimal operating trajectories are calculated by a feedforward, Newton–Raphson method-based searching algorithm that considers the iron loss resistance of IPMSMs. Steady-state calculations and dynamic simulation results prove the theoretical findings.